The Combined Extract of Black Sticky Rice and Dill Improves Poststroke Cognitive Impairment in Metabolic Syndrome Condition. (26th February 2019) - Ohnon, Warin; Wattanathorn, Jintanaporn; Thukham-mee, Wipawee; Muchimapura, Supaporn; Wannanon, Panakaporn; Tong-un, Terdthai
Abstract : Despite the increase in cognitive deficit following stroke in metabolic syndrome (MetS) condition, the therapeutic strategy is still limited. Since oxidative stress and neuroinflammation play the crucial roles on the pathophysiology of aforementioned conditions, the cognitive enhancing effect of the combined extract of Oryza sativa and Anethum graveolens was considered based on their antioxidant, anti-inflammation, and neuroprotective effects together with the synergistic effect concept. Male Wistar rats weighing 180-220 g were induced metabolic syndrome-like condition by using a high-carbohydrate high-fat diet (HCHF diet). Then, reperfusion injury following cerebral ischemia was induced by the occlusion of right middle cerebral artery and treated with the combined extract of O. sativa and A. graveolens (OA extract) at doses of 0.5, 5, and 50 mg/kg BW once daily for 21 days. Spatial memory was assessed every 7 days throughout the experimental period. At the end of the study, neuron and glial fibrillary acidic protein- (GFAP-) positive cell densities, the oxidative stress status, AChE, and the expression of proinflammatory cytokines (TNF- α, IL-6) in the hippocampus were determined. The results showed that OA extract at all doses used in this study significantly improved memory together with the reductions of MDA, TNF- α, IL-6, AChE, and density of GFAP-positive cell but increased neuron density in the hippocampus. Taken together, OA is the potential cognitive enhancer in memory impairment following stroke in MetS condition. The possible underlying mechanism may occur partly via the reductions of oxidative stress status, GFAP-positive cell density, and neuroinflammatory cytokines such as TNF- α and IL-6 together with the suppression of AChE activity in the hippocampus. This study suggests that OA is the potential functional ingredient to improve the cognitive enhancer. However, further clinical research is required.